Axin2 coupled excessive Wnt‐glycolysis signaling mediates social defect in autism spectrum disorders - Mengmeng Wang; Panpan Xian; Weian Zheng; Zhenzhen Li; Andi Chen; Haoxiang Xiao; Chao Xu; Fei Wang; Honghui Mao; Han Meng; Youyi Zhao; Ceng Luo; et al. (EMBO Molecular Medicine, 2023)
Abstract Social dysfunction is the core syndrome of autism spectrum disorder (ASD) and lacks effective medicine. Although numerous risk genes and relevant environmental factors have been identified, the convergent molecular mechanism underlying ASD‐associated social dysfunction remains largely elusive. Here, we report aberrant activation of canonical Wnt signaling and increased glycolysis in the anterior cingulate cortex (ACC, a key brain region of social function) of two ASD mouse models (Shank3−/− and valproic acid‐treated mice) and their corresponding human neurons. Overexpressing β‐catenin in the ACC of wild‐type mice induces both glycolysis and social deficits. Suppressing glycolysis in ASD mice partially rescued synaptic and social phenotype. Axin2, a key inhibitory molecule in Wnt signaling, interacts with the glycolytic enzyme enolase 1 (ENO1) in ASD neurons. Surprisingly, an Axin2 stabilizer, XAV939, effectively blocked Axin2/ENO1 interaction, switched glycolysis/oxidative phosphorylation balance, promoted synaptic maturation, and rescued social function. These data revealed excessive neuronal Wnt‐glycolysis signaling as an important underlying mechanism for ASD synaptic deficiency, indicating Axin2 as a potential therapeutic target for social dysfunction.